The Influence of Self Management Dietary Counseling on The Value of Sodium and Edema in Hemodialysis Patients - Faradisa Yuanita Fahmi; titik hidayati; Nur Chayati (Media Keperawatan Indonesia, 2019)
Background: Reducing salt care & reducing fluid intake is one of the efforts to prevent fluid imbalance in patients. The increase in the prevalence of events that occur in hemodialysis patients is caused by various factors, one of which is inaccuracy in doing therapy. Self Management Dietary Counseling (SMDC) aims to increase patient knowledge and participate in health decision making to improve patient compliance and clinic outcome. Purposes: Knowing the effect of Self Management Dietary Counseling (SMDC) on the value of sodium in hemodialysis patients. Methode: Quasy Experiment, pretest-post-test design, 60 samples consisted of 3 groups. Sampling using a random sampling technique. Result: the group treated with SMDC has a p-value <0.050, while the non-treated group has a p value> 0, 050. Conclusion: Self Management Dietary Counseling has an effect on the value of sodium in hemodialysis patients. This study recommends that nurses apply SMDC to each hemodialysis patient to improve the value of sodium.